Molecular mechanism of leaf adaxial upward curling caused by BpPIN3 suppression in Betula pendula - Chen, Kun; Qu, Chang; Zhang, Xiao-yue; Wang, Wei; Gu, Chen-rui; Liu, Gui-feng; Yu, Qi-bin; Yang, Chuan-ping; Jiang, Jing (Frontiers in Plant Science, 2022)
Leaves are one of the vegetative organs of plants that are essential for plant growth and development. PIN-FORMED (PINs) gene is an indoleacetic acid (IAA) transporter that plays a critical role in leaf development. To determine the function of BpPIN3 in leaf polarity formation in Betula pendula, the transgenic lines with BpPIN3 overexpression (OE) and RNAi knockdown (RE) were analyzed using the Agrobacterium-mediated method. The RE lines displayed the characteristics of leaf margin adaxial upward curling, with lower expression of BpPIN3 resulting in greater rolling. Tissue localization of IAA in the auxin GUS reporter system proved that auxin in the RE was mainly distributed in the secondary veins, palisade tissues, and epidermal cells in the leaf margin area. The auxin content in the leaf margin area was significantly greater than that in the main vein tissue. The cell density of the palisade tissue and the ratio of palisade tissue to spongy tissue in the curled leaf margin of the RE lines were found to be significantly decreased. RNA-seq analysis revealed that the RE hormone-signaling pathway genes were significantly enriched compared with those of the OE and WT lines; in particular, the auxin response-related genes SAURs (i.e., SAUR23, SAUR24, SAUR28, and SAUR50) and GH3.10 were found to be significantly upregulated. qRT-PCR analysis indicated that BpPIN3 expression at the leaf margin was significantly lower than that near the main vein in the RE lines. In contrast, the expression levels of SAURs and GH3.10 were significantly higher than those near the midrib. In conclusion, BpPIN3 regulates the expression of auxin response-related genes and the polar transport of auxin to change the polar form of the proximal and distal axes of birch leaves.